The Meaning of the Compiler between the Two Concerned in Arabic - Adnan Hassan, Ashraf; Abdel Latif Saber, Nizar (International Journal of Psychosocial Rehabilitation, 2020)
This study deals with the significance of the mosque between the two concerned in Arabic, in the light of the science of meanings and statements, especially in the chapters of the Musnad and assigned to it, analogy and metaphor, in its various sections, with a statement of homogeneity or convergence between the two parties, and the similarities and differences between these mosques.